1989
DOI: 10.1021/bi00438a043
|View full text |Cite
|
Sign up to set email alerts
|

Expression of two kallikrein gene family members in the rat prostate

Abstract: We have characterized two kallikrein gene family members expressed in the prostate and submaxillary glands of rats. One mRNA (S3) is identical with the previously characterized submaxillary gland S3 mRNA that encodes an enzyme closely related to tonin. The second mRNA (P1) encodes a novel kallikrein-like enzyme that retains key amino acid residues responsible for the characteristic enzymatic cleavage specificity of kallikrein. Two P1-specific oligonucleotide probes derived from the P1 mRNA sequence were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 57 publications
3
17
0
Order By: Relevance
“…Mouse kallikrein expression in the prostate has not yet been demonstrated. Two members of the closely related rat kallikrein gene family have been found to be expressed in both prostate and submandibular gland (17). To compare PSA promoter specificity in transgenic mice with the promoter specificity of endogenous mouse kallikreins, we determined which, if any, of the mouse kallikrein genes was expressed in prostate.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse kallikrein expression in the prostate has not yet been demonstrated. Two members of the closely related rat kallikrein gene family have been found to be expressed in both prostate and submandibular gland (17). To compare PSA promoter specificity in transgenic mice with the promoter specificity of endogenous mouse kallikreins, we determined which, if any, of the mouse kallikrein genes was expressed in prostate.…”
Section: Introductionmentioning
confidence: 99%
“…Several proteins of the kallikrein family have been purified from the rat submandibular gland (SMG), including rK8 (Elmoujahed et al, 1990), which is identical to P1 (Brady et al, 1989), and rK9, which has previously been named prostatic protease (Winderickx et al, 1989). SEV (Yamaguchi et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In human prostate, two kallikrein-like genes have been detected, and one of these has been identified as the gene encoding prostate-specific antigen (Lundwall and Lilja, 1987;Schedlich et al, 1987). In rat prostate, two "As, rKlk8 (formerly mRNA PI) and rKlk9 (formerly mRNA S3), have been sequenced (Brady et al, 1989;Winderickx et al, 1989). Recently, the corresponding proteins for these two kallikrein-like "As, rK8 and rK9, have been purified from the rat ventral prostate, whereas other proteins of the kallikrein family were not detected (Schpyen et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Previous Northern hybridization analyses of the expression patterns of individual rat and mouse family members suggested that the expression of each might be limited to a few organs, and that these sites were often shared by different members (see e.g., Wines et al, 1989;van Leeuwen et al, 1986;Ashley and MacDonald, 1985b;Brady et al, 1989;Clements et al, 1990;Ma et al, 1992). Comparisons were constrained, however, because generally few organ sites were examined, and those examined were often different for various family genes.…”
mentioning
confidence: 99%